Real World COPD: Association of Morning Symptoms with Clinical and Patient Reported Outcomes. (1st December 2013) - Roche, Nicolas; Small, Mark; Broomfield, Sarah; Higgins, Victoria; Pollard, Ryan
Abstract This research examined the prevalence of morning symptoms and their relationship with health status, exacerbations and daily activity in patients with chronic obstructive pulmonary disease (COPD). Data on 1489 patients were analysed from a European and USA sample. Results were tested for significance (p < 0.05) using Mann-Whitney and regression modelling accounting for age, gender, body mass index, comorbidities, symptom severity, smoking status and medication adherence. Morning symptoms were experienced by 39.8% of patients. Controlling for potential confounders, morning symptoms were significantly associated with higher COPD assessment test scores (p < 0.001) and exacerbation frequency (p < 0.001), more frequent worsening of symptoms without consulting a Health Care Professional (p = 0.008), and increased impact on normal daily activities (p = 0.007); and in the working population, a significantly greater impact on getting up and ready for the day (p < 0.001) and significantly more days off work per year (p < 0.001). Our research concluded that in patients with COPD, morning symptoms are associated with poorer health status, impaired daily activities and increased risk of exacerbation in affected patients compared with those patients without morning symptoms. Improved control of patients' morning symptoms may lead to substantial reduction in COPD impact and frequency of exacerbations, and enable patients to increase daily activities, particularly early morning activities. This could, in turn, enable working patients with COPD to be more productive in the workplace.